Update on Respiratory Fungal Infections in Cystic Fibrosis Lung Disease and after Lung Transplantation - Sabine Renner; Edith Nachbaur; Peter Jaksch; Eleonora Dehlink (Journal of Fungi, 2020)
Cystic fibrosis is the most common autosomal-recessive metabolic disease in the Western world. Impaired trans-membrane chloride transport via the cystic fibrosis transmembrane conductance regulator (CFTR) protein causes thickened body fluids. In the respiratory system, this leads to chronic suppurative cough and recurrent pulmonary infective exacerbations, resulting in progressive lung damage and respiratory failure. Whilst the impact of bacterial infections on CF lung disease has long been recognized, our understanding of pulmonary mycosis is less clear. The range and detection rates of fungal taxa isolated from CF airway samples are expanding, however, in the absence of consensus criteria and univocal treatment protocols for most respiratory fungal conditions, interpretation of laboratory reports and the decision to treat remain challenging. In this review, we give an overview on fungal airway infections in CF and CF-lung transplant recipients and focus on the most common fungal taxa detected in CF, Aspergillus fumigatus, Candida spp., Scedosporium apiospermum complex, Lomentospora species, and Exophiala dermatitidis, their clinical presentations, common treatments and prophylactic strategies, and clinical challenges from a physician’s point of view.